CATALAN COLLOCATIONS TAU METHOD FOR SOLUTION OF FRACTIONAL INTEGRO-DIFFERENTIAL EQUATIONS - Isiyaku, Musa; Amos, Jerry; Oladoja, Adebayo S.; Chukkol, Y. B.; Jingi, Bala M. (FUDMA JOURNAL OF SCIENCES, 2025)
This article is concern with the numerical solution of Fractional order Fredholm Integro-differential Equations using Catalan tau collocation method. The concept of Catalan tau collocation method was implemented on some of fractional Fredholm integro-differential equations to illustrate the efficienciency and practicability of the method. Fractional derivatives in Riemann-Liouvilles sense were adopted throughout this article.. The results showed the reliable, efficacy and accuracy that the method exhibited for this kind of problems when compared to the analytic solutions.